The Relationship between Body Image and Bullying Behavior among Adolescents at SMK Bunga Persada Cianjur - Inggit Sri Kusdiyanty; Victoria Firman Widouzan; Vironica Rahmantio; Sephia Rapiani Hardiana (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Bullying is a psychosocial problem widely experienced by adolescents and has a serious impact on mental health and social development. One of the associated factors is body image. Objective: This study aimed to determine the relationship between body image and bullying behavior among adolescents at SMK Bunga Persada Cianjur in 2025. Method: This study used a quantitative correlational design with a cross-sectional approach. The population consisted of 291 eleventh-grade students, with 168 respondents determined using the Slovin formula. The research instruments were body image and bullying questionnaires. Data were analyzed using the Chi-Square test at a significance level of 0.05. Result and Discussion: Ninety-four respondents (56.0%) had a positive body image and 74 respondents (44.0%) had a negative body image. Seventy-nine respondents (47.0%) experienced bullying and 89 respondents (53.0%) did not. The Chi-Square test showed a significant relationship between body image and bullying behavior (p = 0.000; p < 0.05). Conclusions: There is a significant relationship between body image and bullying behavior among adolescents. The more positive an adolescent's body image, the lower their tendency to be involved in bullying